The construction of the identity of political prisoner´s wives (1959–1977) - Álvarez Maylín, Carlota (Hispania Nova, 2019)
This article seeks to analyze the construction process of “prisoner´s wife” identity through the letters written by the political prisoners´ wives, under the campaign for general Amnesty that were developed during the Francoist regime. This objective is approached by using gender perspective, which allows us to study the imposition of traditional gender roles on these women; and from Written Culture History as a way to understand the contents of those letters of pleading, and the “prisoner’s wife” identity changes, on which they had a common reference and mutual lived reality.